A Study Of ‘Ageing In Place’(Aip) In Malaysia: An Exploration And Understanding Of The Everyday Life Of Old People In Ipoh - Chan, Cecilia Woen Min (2021)
The aim of this thesis is to explore and understand the everyday life of old people who are ageing in place in Ipoh. The research focuses on the meaning of ageing in place for the older people in Ipoh. A total of eighty participants aged 65 and above from Ipoh were involved in this study. Using an Abductive Research Strategy (ARS) as the methodology this research generates social scientific accounts from social actors’ (older people’s) accounts. Sampling methods including purposive, snowball, and theoretical were adopted. In-depth interviews followed up with participatory observation were the main research methods utilised in this study.